URGENSI DAN STUDI ISLAM - M. Syahdan Al-Bantani; Rizky Maulana; Nadzifah Arzaqillah; Maftuh Ajmain (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Islamic Studies is a discipline that systematically and comprehensively examines the teachings, history, thought, and religious phenomena of Islam. The urgency of Islamic Studies becomes crucial in the modern era, which is characterized by globalization, technological advancement, secularization, radicalism, and an overwhelming flow of unfiltered information. Without a deep understanding through Islamic Studies, a person is vulnerable to misinterpretation of religious proofs, religious hoaxes, erroneous interpretations, and extremist ideologies that damage the image of Islam. Islamic Studies has a strategic role in preserving the purity of Islamic teachings, forming noble character in accordance with the prophetic mission, answering contemporary problems with solutions based on Islamic values, and building a civilization for the Muslim community as exemplified by past Muslim scholars such as Ibn Sina and Al-Khawarizmi. The relationship between urgency and Islamic Studies is very close, where urgency serves as the fundamental reason why Islamic Studies must be studied, while Islamic Studies is the field of knowledge to be learned. In conclusion, studying Islamic Studies is a vital necessity for every Muslim in order to practice Islam comprehensively (kaffah) and become a mercy to all worlds (rahmatan lil 'alamin) amidst the challenges of the modern era.